The Effect of Intrathecal Bupivacaine Plus Dextrose 5% and Fentanyl Compared with Bupivacaine Alone on the Onset and Duration of Analgesia in Patients Undergoing Lower-Limb Orthopedic Surgery - Amir Sabertanha; Gholam Reza Makhmalbaf; Maryam Bayati; Aram Meshkini (Advances in Orthopedics)
Introduction. This study aimed to compare the effect of intrathecal bupivacaine plus dextrose 5% and fentanyl with bupivacaine alone on the onset and duration of analgesia in patients undergoing lower-limb orthopedic surgery. Materials and Methods. A total of 40 patients eligible for lower-limb surgery were divided into two groups by simple randomization: the control group which received only bupivacaine and the intervention group which received bupivacaine plus dextrose 5% and fentanyl. Anesthesia was induced by the spinal method. The visual analog scale (VAS) was used to assess the patients’ pain; hemodynamic status (systolic and diastolic blood pressure and the heart rate) and oxygen saturation were also monitored. Results. There was a significant difference between groups in the type of lower-limb movement at the L1 anesthesia level, the sensory block level at time zero after surgery, the type of backward movement at time zero after surgery, and the analgesic dose received (p<0.05). Fifteen and 30 minutes after the start of surgery, mean systolic blood pressure, and 45 and 60 minutes after the start of surgery, systolic and diastolic blood pressure and the heart rate were significantly lower in the control group than in the intervention group (p<0.05). The VAS score was significantly lower in the intervention group than in the control group at 6 and 24 hours after surgery (p<0.05). Systolic and diastolic blood pressure at time zero, systolic blood pressure at hour 6, and diastolic blood pressure at hour 24 after surgery were significantly lower in the control group than in the intervention group (p<0.05). Conclusion. The mean duration of anesthesia and analgesia was significantly longer in patients receiving bupivacaine plus fentanyl than in those receiving bupivacaine alone. However, concerning hemodynamic parameters, it cannot be concluded that the bupivacaine plus fentanyl receiving group was generally superior to the bupivacaine receiving group.